2018
DOI: 10.3390/ijerph15112580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar Amendment on CO2 Emissions from Paddy Fields under Water-Saving Irrigation

Abstract: The role of carbon pool of biochar as a method of long-term C sequestration in global warming mitigation is unclear. A two-year field study was conducted to investigate the seasonal variations of CO2 emissions from water-saving irrigation paddy fields in response to biochar amendment and irrigation patterns. Three biochar treatments under water-saving irrigation and one biochar treatment under flooding irrigation were studied, and the application rates were 0, 20, 40, and 40 t ha−1 and labeled as CI + NB (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Explaining the rate of adsorption, carbon sequestration, and GHGs emissions in the soil‐biochar complex lies in the characteristics of the biochar (Giles et al, 2017). CO 2 emissions primarily depend on carbon content in biochar‐soil complex (S. Yang et al, 2018). Biochar forms complexes with soil aggregates (Xiao, Zhang, et al, 2016) which decreases the rate of soil enzymatic activities (Demisie et al, 2014) and creates organic macromolecules such as aromatics that are difficult to use by microorganisms (Gorovtsov et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Explaining the rate of adsorption, carbon sequestration, and GHGs emissions in the soil‐biochar complex lies in the characteristics of the biochar (Giles et al, 2017). CO 2 emissions primarily depend on carbon content in biochar‐soil complex (S. Yang et al, 2018). Biochar forms complexes with soil aggregates (Xiao, Zhang, et al, 2016) which decreases the rate of soil enzymatic activities (Demisie et al, 2014) and creates organic macromolecules such as aromatics that are difficult to use by microorganisms (Gorovtsov et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Farmland, which contributes 7–20% of the world’s total greenhouse gas emissions [ 9 ], is a proven contributor to carbon emissions. In particular, paddy fields are generally considered to be significant contributors to net carbon emissions [ 10 ]. Forest ecosystems are one of the largest terrestrial ecosystem carbon pools, and the carbon storage of forest ecosystems accounts for 50–60% of the world’s carbon storage [ 11 ]; hence, the carbon storage potential of forests has motivated the research interest of many scientists [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, biochars have high potential to sequester carbon, thus reducing soil CO 2 emission [24,25]. Several studies reported elevated CO 2 emission after biochar usage [26,27], while others found reduced CO 2 emissions [28,29]. Positive or negative effects of biochar usage on soil GHG emission are not only highly dependent on soil structure but also on biochar parameters such as its type or pyrolysis temperature [30,31].…”
Section: Introductionmentioning
confidence: 99%